2021
DOI: 10.1186/s13018-021-02840-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endplate coverage and intervertebral height change on heterotopic ossification following cervical disc replacement

Abstract: Background Heterotopic ossification (HO) is a common complication after cervical disc replacement (CDR). Biomechanical factors including endplate coverage and intervertebral disc height change may be related to HO formation. However, there is a dearth of quantitative analysis for endplate coverage, intervertebral height change and their combined effects on HO. Methods Patients who underwent single-level or two-level CDR with Prestige-LP were retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Due to the load-bearing capabilities and complexity of motion exposure to daily activities, the importance of evaluating the material characteristics of the prosthesis intended to replace the disc cannot be underestimated. Furthermore, current failures associated with existing implants, such as heterotopic ossification, insufficient stiffness, dislocation, wear and improper ICR further buttress the need for assessing the mechanical behavior of a material proposed to replace the disc ( Virk et al, 2021 ; Shen et al, 2021 ; Shen et al, 2022 ; Cao et al, 1976 ; Parish et al, 2020 ). Thus, an appropriate material attribute design using a PE core and PCU fiber jacket with adequate native geometry could represent a suitable candidate for replacing the disc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the load-bearing capabilities and complexity of motion exposure to daily activities, the importance of evaluating the material characteristics of the prosthesis intended to replace the disc cannot be underestimated. Furthermore, current failures associated with existing implants, such as heterotopic ossification, insufficient stiffness, dislocation, wear and improper ICR further buttress the need for assessing the mechanical behavior of a material proposed to replace the disc ( Virk et al, 2021 ; Shen et al, 2021 ; Shen et al, 2022 ; Cao et al, 1976 ; Parish et al, 2020 ). Thus, an appropriate material attribute design using a PE core and PCU fiber jacket with adequate native geometry could represent a suitable candidate for replacing the disc.…”
Section: Discussionmentioning
confidence: 99%
“…The preservation of physiologic motion at the treated level leads to longevity of the facet joints and decreases the adjacent segment degeneration rate, which would otherwise lead to additional revision surgery ( Bhattacharya et al, 2019 ; Rajakumar et al, 2017 ; Yang et al, 2017 ). Ball-and-socket TDR have been more popular than other designs in recent years, but their potential disadvantages include polyethylene (PE) wear, heterotrophic ossification, increased contact forces, and disc subsidence and migration ( Virk et al, 2021 ; Shen et al, 2021 ; Shen et al, 2022 ; Cao et al, 1976 ; Parish et al, 2020 ). A new-generation prosthesis with a compressible central core allows for six kinematic degrees of freedom and mimics normal biomechanics has been developed and used ( Patwardhan et al, 2012 ; Phillips et al, 2021 ; Oltulu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al 4) have iterated that a more than 5° increase in immediate post-operative disc space angle and less segmental ROM have conferred a negative effect on HO formation. Meanwhile, Shen et al 10) have previously concluded that endplate coverage of less than 93.8% or intervertebral height change of more than 1.8 mm would exacerbate the non-uniform distribution of stress in the bone-implant interface and promote posterior HO development after cervical disc replacement. Further investigations are warranted to corroborate these risk factors, including multilevel calcified disc herniation, severe spondylosis, and suboptimal placement of the device during primary cervical disc replacement surgery.…”
Section: Wwwthenervenetmentioning
confidence: 99%
“…18 Possible solutions to decrease the risk of HO is to attempt to restore physiologic disk height and to ensure the implant covers more than 93% of the end plate. 19…”
Section: Preservation Of Motion In the Cervical Spinementioning
confidence: 99%
“…18 Possible solutions to decrease the risk of HO is to attempt to restore physiologic disk height and to ensure the implant covers more than 93% of the end plate. 19 Subsidence of cervical ADA devices has been reported to occur in zero to 33% of cases and at a time frame of up to 4 years after implantation. Subsidence can cause issues such as axial neck pain and recurrent radiculopathy because of loss of foraminal height.…”
Section: Complicationsmentioning
confidence: 99%